Pengaruh Morfin Terhadap Pertumbuhan Kartilago Epifisialis Os Tibia Fetus Mencit (Mus Musculus L.) - Arum Setiawan (Jurnal Penelitian Sains, 2002)
This experiment was performed to examine the eﬁeets of Morphine on growth of foetuses tibia epiphyseal cartilage in pregnant mice at the organogenesispaiod. Thirty pregnant mice were divided randomly into 5 groups of 6. Morphine nus dissolved in aquabides and administrated intranamuscular on sixth to fifteenth days of gestation. Morphine was given at the dosage of 0. 02; 0.05 and 0. I3 mg/20g.body weight, respectively. The remaining aninmls were used as controls and placebo group. At eighteenth day of gestations, the pregnant na'ce were sacriﬁced and caesarian sectioned to remove the foetuses. The growth of tibia epiphyseal cartilages were observed histologically using Erlich ’s Hematoxylin-Eosin stain. Result of these studies indicated that morphine given to the pregnant mice at the organogenesis period caused decreased thickness of the rest zone, proliferative zone, maturation zone, and calcﬁication zone on the foetus tibial growth plate signicantly.